Latchup characterization of submicrometer CMOS - Chow, Jane Sze Mun. (2008)
The main purpose of this project is to study the latchup phenomenon in submicrometer CMOS devices and investigate the effects of spike annealing process on latchup sensitivity. Latchup characterization was carried out by a steady-state latchup triggering method.